Diastolic blood pressure predicts coronary plaque volume in patients with coronary artery disease. (October 2018) - Saleh, Mohamad; Alfaddagh, Abdulhamied; Elajami, Tarec K.; Ashfaque, Hasan; Haj-Ibrahim, Huzifa; Welty, Francine K.
Abstract: Background and aims: Hypertension is associated with increased clinical and subclinical coronary artery disease (CAD); however, the relationship between blood pressure and coronary plaque volume is unclear. We examined the effect of systolic blood pressure (SBP) and diastolic blood pressure (DBP) on coronary artery plaque volume. Methods: 285 subjects with stable CAD on statin therapy underwent coronary computed tomographic angiography to measure volume of fatty, fibrous, noncalcified, calcified and total coronary plaque. Results: Mean (SD) age was 63.1 (7.7); mean (SD) LDL-C, 78.7 mg/dL (28.5). Compared to the highest DBP tertile (>76 mmHg), those in the lowest DBP tertile (≤68 mmHg) had lower volumes of fatty: 10.0 vs. 7.7 mm 3 /mm, ( p trend = 0.042), fibrous: 19.6 vs. 13.8 mm 3 /mm ( p trend = 0.011), non-calcified: 29.7 vs. 22.5 mm 3 /mm ( p trend = 0.017) and total plaque: 37.8 vs. 25.1 mm 3 /mm ( p trend = 0.010) whereas there was no relationship with SBP tertiles. Similarly, when examined as a continuous variable, higher DBP was a significant independent predictor of higher plaque volume after multivariate adjustment: for every 1 mmHg increase in DBP, fibrous plaque increased 0.128 mm 3 /mm ( p  = 0.022), noncalcified plaque increased 0.176 mm 3 /mm ( p  = 0.045), calcified plaque increased 0.096 mm 3 /mm ( p  = 0.001) and total plaque increased 0.249 mm 3 /mm ( p  = 0.019) whereas SBP ranging from 95 to 154 mmHg did not predict plaque volume. Conclusions: Level of DBP predicts coronary plaque with a DBP tertile ≤68 mmHg associated with the least amount of coronary plaque in subjects with LDL-C < 80 mg/dL. Highlights: Coronary plaque volume was measured by coronary computed tomographic angiography. Coronary plaque volume was higher at higher levels of diastolic blood pressure. In contrast, systolic blood pressure did not predict coronary plaque volume. Diastolic blood pressure ≤68 mm Hg had the lowest coronary plaque volume. Reduction of diastolic blood pressure to ≤68 mm Hg may prevent plaque progression.